Seasonal incidence of Haritalodes derogata (Fabricius)(Lepidoptera, Crambidae) on Urena lobata in Saharanpur, Uttar Pradesh, India - Datta, Om (ENTOMON, 2026)
A field study was conducted to determine the seasonal incidence of Haritalodes derogate on Urena lobata weed in Saharanpur, Uttar Pradesh, during the year 2023-2024. The study revealed that H. derogata is a serious pest of U. lobata and its activity began in the first week of June and continued until December of 2023 and 2024. The larval population was minimum in June, with the lowest leaf damage. In contrast, the maximum population was observed in September and October, with the highest damage per leaf and per plant during the year 2023 and 2024. The pest remained active from June to December during both years.